Genome-Wide Identification and Characterisation of Abiotic Stress Responsive mTERF Gene Family in Amaranthus hypochondriacus - Hajyzadeh, Mortaza (Tech Science Press, 2023)
Abiotic stresses at different growth stages in the life of plants negatively affect yield productivity. Therefore, plants, including Amaranthus hypochondriacus, develop adaptive strategies to face the stresses and expand functional diversification. In plants, the mitochondrial transcription termination factors (mTERF) are essential functions in regulation, and organelles (mitochondria and chloroplasts) control gene expression (OGE) under several stress conditions. Based on the in-silico-wide genome and transcriptome analysis, twenty-four mTERF genes were detected in the main targeted mitochondria organelles clustered into three different main groups. The chromosomal location and gene duplication analysis indicated one segmental and one tandem duplication in the genome. The promoter region cis-elements assessment showed that there wasa high correlation between the growth and development process, stress, and hormone responses of these genes. Expression profiling of mTERF genes under salt stress revealed a total number of 24 gene families with seven upregulated and 6 down-regulated genes in drought and salt stress. However, Ah-mTERF-8 and 14 indicated up-regulation under drought stress. Ah-mTERF-4, 6, 14, 15, 17, and 20 were up-regulated under salt stress. Molecular characterization and identification through the in-silico study of the specific genes and their differential expression profiling demonstrated the role of mTERF proteins throughout their reaction to growth and development, during stress in A. hypochondriacus. These results demonstrated that mTERF genes were significantly related to the abiotic stress responses.
Keywords: Genus Amaranthus mTERF protein; mitochondria; RNA-seq; transcription; salt and drought stress